‘Women, forgive us’: A German case study - Volker Kessler (HTS Teologiese Studies/Theological Studies, 2022)
This article offers insight into the image of women in German conservative congregations, especially in the Brethren movement. It also describes the author’s personal journey to a position of strongly supporting female preaching and female leadership in churches. The article combines empirical facts and personal insights. It gives examples of androcentrism in German academic theology. The case study is on the Brethren movement in Germany and their teaching on women, which was very much influenced by certain Pauline texts from the New Testament. Unfortunately, ‘women’s role in the church’ became the shibboleth for biblical correctness. While living and working in this context, the author discovered inconsistencies in practice, which finally led to this paradigm shift.